2017
DOI: 10.1214/16-aos1495
|View full text |Cite
|
Sign up to set email alerts
|

Tests for separability in nonparametric covariance operators of random surfaces

Abstract: Abstract. The assumption of separability of the covariance operator for a random image or hypersurface can be of substantial use in applications, especially in situations where the accurate estimation of the full covariance structure is unfeasible, either for computational reasons, or due to a small sample size. However, inferential tools to verify this assumption are somewhat lacking in high-dimensional or functional data analysis settings, where this assumption is most relevant. We propose here to test separ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 28 publications
0
67
0
Order By: Relevance
“…Kokoszka et al (2016), Gromenko et al (2016Gromenko et al ( , 2017, French et al (2016), Tupper et al (2017), Liu et al (2017), and Shang and Hyndman (2017). Testing separability of spatiotemporal functional data of the above form is investigated in Constantinou et al (2017), Aston et al (2017), and Bagchi and Dette (2017) under the assumption that the fields X n (⋅, ⋅), 1 ≤ n ≤ N, are independent. No tests are currently available for testing separability in the presence of temporal dependence across n. In a broader setting, the data that motivate this research have the form of functional panels: X n (t) = [X n1 (t), X n2 (t), ..., X nS (t)] T , 1 ≤ n ≤ N.…”
Section: Introduction Supposementioning
confidence: 99%
“…Kokoszka et al (2016), Gromenko et al (2016Gromenko et al ( , 2017, French et al (2016), Tupper et al (2017), Liu et al (2017), and Shang and Hyndman (2017). Testing separability of spatiotemporal functional data of the above form is investigated in Constantinou et al (2017), Aston et al (2017), and Bagchi and Dette (2017) under the assumption that the fields X n (⋅, ⋅), 1 ≤ n ≤ N, are independent. No tests are currently available for testing separability in the presence of temporal dependence across n. In a broader setting, the data that motivate this research have the form of functional panels: X n (t) = [X n1 (t), X n2 (t), ..., X nS (t)] T , 1 ≤ n ≤ N.…”
Section: Introduction Supposementioning
confidence: 99%
“…In many settings, formulae become much simpler if normality is assumed (e.g. Panaretos et al, 2010;Kraus and Panaretos, 2012;Fremdt et al, 2013;Aston et al, 2017). A test that verifies that the assumption of normality is reasonable for a sample of curves will bolster confidence in the conclusions of these and many other functional data analysis (FDA) procedures.A well-known challenge of working with functional data is that, to perform computations, data must be reduced to finite-dimensional objects.…”
mentioning
confidence: 99%
“…As Aston et al . () have already found that the separability assumption does not hold for the acoustic phonetic data, it would be interesting to see how the results of this paper change without assuming a separable covariance structure (e.g. Kang et al .…”
Section: Discussion On the Paper By Pigoli Hadjipantelis Coleman Anmentioning
confidence: 82%
“…The results of the paper and the definition of a path and a transformation operator from one language to another in Section 6 appear to depend considerably on this separability assumption; thus it seems necessary to conduct a test for separability (see Aston et al . () and Constantinou et al . ()).…”
Section: Discussion On the Paper By Pigoli Hadjipantelis Coleman Anmentioning
confidence: 85%